KEBERMAKNAAN HIDUP DALAM ORGANISASI BERBASIS PAGUYUBAN: PERSPEKTIF PSIKOLOGI POSITIF - Yudhawati, Dian; Pabbajah, Mustaqim (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
Activities in a non-profit organization require sincerity and energy to carry out various activities within it without expecting imbalance. This research discovers how meaningful the lives of the members of the Paguyuban Babarsari Satu (PBS) organization, the alumni of the UPN “Veteran” Yogyakarta Student Regiment Organization. This research is qualitative research with a descriptive narrative method. Data were collected using semi-structured interviews, then analyzed using thematic approach. The informants are members of the organization who have been active for at least 10 years. The results of this research show that in the aspect of understanding, PBS members have motivation to help other people who need their help. In the aspect of targeted-activities, members increase their ability to build relationships for happiness through as a sense of kinship as well as businesses and hobbies to be developed together. In the aspect of personal bonding, PBS members remain persistent and persevere despite the many difficulties they experience. Furthermore, experiencing a change in attitude to become more positive from before joining until now they have joined as members of PBS. In the aspect of social support, PBS members get support from those closest to them. Then in the aspect of the meaning of life, PBS members want to be useful and be able to do more for the PBS organization. These findings provide another perspective in the study of positive and community psychology as well as implications for the development of interventions to improve individual well-being in community-based social groups.